Developing a Classification Schema for the Discipline of GIS: Based on the Dewey Decimal Classification (DDC) System: A knowledge Structure based Approach - Karunarathne, A (VDM Verlag Dr. Muller Aktiengesellschaft & Co. KG, 2011)
The developed Classification Schema, was based on an enumerative (considered Arabic numeric) system and consists of a hierarchical approach. The developed Knowledge Structure enclosed most of existing terminologies of GIS. The selected discipline was classified as a sub-discipline of the main discipline of Geography. Furthermore, user community, major topics of interest, controlled vocabularies, existing sources on discipline, codes, abbreviations, multiple occurrences, parallel hierarchies etc. were considered. Finally, analyzed information were included to the developed Knowledge Structure and it mainly consists of Classification Schema and Relative Indexes. According to the referenced relative information, the analysis were revealed that the developing of such a knowledge structure for a digital library on a dynamic discipline is more significant for the academic and research world. Therefore, the compiled Classification Schema will play a vital role in providing valuable information for the users who are specially working with the discipline of Geographical Information Systems (GIS)and Spatial Information Management.